SINO Syndrome Causative KIDINS220/ARMS Gene Regulates Adipocyte Differentiation - Zhang, Kaihui; Sun, Wenxing; Liu, Yi; Lv, Yuqiang; Hou, Daisen; Lin, Yan; Xu, Wei; Zhao, Jianyuan; Gai, Zhongtao; Zhao, Shimin; Yuan, Yiyuan (Frontiers in Cell and Developmental Biology, 2021)
Nonsense variants in KIDINS220/ARMS were identified as the main cause of SINO syndrome, a rare disease with birth defects in brachycephaly, neurological disorder and obesity. The cause of neural cell dysfunction by KIDINS220/ARMS were extensively studied while the cause of obese in SINO syndrome remains elusive. Here, we identified KIDINS220/ARMS as an adipocyte differentiation-regulating gene. A Chinese family, mother and her two sons, all showed severe symptoms of SINO syndrome. G-banding karyotyping, Chromosome microarray analysis and Whole exome sequencing revealed a novel amber mutation, c.3934G>T (p.E1312X), which was close to the C-terminal region of KIDINS220/ARMS and resulted in the premature of the protein. Both the mRNA and protein levels of KIDINS220/ARMS gradually decreased during adipocyte differentiation. Knockdown of KINDINS220/ARMS could prompt adipocyte differentiation and lipid accumulation while overexpression of KIDINS220/ARMS decrease the rate of matured adipocytes. Furthermore, we demonstrated that KIDINS220/ARMS inhibits adipocyte maturation through sustained ERK signaling. In conclusion, this is the first report about a vertical heredity of severe dominant pathogenic mutation of KIDINS220/ARMS, suggested that KIDINS220/ARMS plays a negative role in adipocyte maturation, explained the cause of obese in SINO syndrome and may highlight the importance of adipocyte differentiation in neuron functions.